Mechanical Strength Optimization of Alkali-Activated MK/GBFS Binary Cements Through the Response Surface Methodology (2014)
The present article shows the compressive strength modeling and optimization for a non-conventional binder free of clinker, which was produced by the alkali activation of a binary mixture of metakaolin (MK) and a granulated blast furnace slag (GBFS). AGBF